PTH-088 Assessing fatigue in inflammatory bowel disease comparison and validation of three fatigue scales: ibd-f, mfi and maf scales. (22nd June 2015) - Czuber-Dochan, WJ; Norton, C; Bassett, P; Berliner, S; Bredin, F; Darvell, M; Forbes, A; Gay, M; Ream, E; Terry, H
Abstract : Introduction: Patients with inflammatory bowel disease (IBD) report fatigue in both quiescent (41%) and active disease (86%); 1 however, due to its subjective nature it is difficult to assess. Many different fatigue scales exist, although most have not been tested with IBD populations. Only one scale has been developed specifically for people with IBD. 2 We aimed to assess validity and reliability of three fatigue assessment scales in an IBD adult population and to determine factors correlated with fatigue. Method: A cross-sectional study. Participants (n = 605) were randomly selected and completed questionnaires assessing fatigue, anxiety, depression, quality of life and IBD activity. A sub-group of responders (n = 70) were sent the same mailing 6 weeks later for test-retest. The fatigue scales used were: the Inflammatory Bowel Disease Fatigue (IBD-F), the Multidimensional Fatigue Inventory (MFI) and the Multidimensional Assessment Fatigue (MAF). Internal consistency was measured by Cronbach's alpha and test-retest reliability by the intra-class correlation coefficient (ICC). Results: 465 (77%) questionnaires were completed for the test and 69% for retest. All three scales are highly correlated (p < 0.001). Test-retest suggests good agreement for all scales' total scores with ICC values of 0.74 and 0.83 (IBD-F Section 1 and 2), 0.74 (MAF) and 0.65–0.84 (MFI). Age, gender, bowel condition, anxiety, depression and IBDQ scores were significantly associated with level of fatigue (p < 0.001) for all three fatigue scales. Older patients had lower fatigue scores, females had higher scores than males, colitis patients had significantly lower scores than Crohn's patients, patients with a higher level of anxiety and depression had higher fatigue scores and better IDBQ was associated with lower fatigue scores. Conclusion: All three tested fatigue scales were found to be valid and reliable measures of IBD fatigue. Factors such as age, gender, bowel condition, quality of life, anxiety and depression are significantly associated with fatigue and should all be taken into account in the process of care delivery to people with IBD and fatigue. Disclosure of interest: W. Czuber-Dochan Grant/ Research Support from: Big Lottery Fund in collaboration with Crohn's and Colitis UK, Speaker Bureau of: Dr Falk Pharma UK, Ferring, C. Norton Grant/ Research Support from: Big Lottery Fund in collaboration with Crohn's and Colitis UK, Speaker Bureau of: Ferring, Shire, P. Bassett: None Declared, S. Berliner Conflict with: Trustee for Crohn's and Colitis UK, F. Bredin Grant/Research Support from: Service development awards from Shire and ferring, M. Darvell Employee of: Crohn's and Colitis UK, A. Forbes Grant/ Research Support from: Big Lottery Fund in collaboration with Crohn's and Colitis UK, Speaker Bureau of: Dr Falk UK, Warner-Chilcott, NPS, M. Gay Consultant for: Crohn's and Colitis UK, Conflict with: Trustee for Crohn's and Colitis UK, E. Ream: None Declared, H. Terry Employee of: Crohn's and Colitis UK References: Czuber-Dochan W, Ream E, Norton C. Review article: description and management of fatigue in inflammatory bowel disease. Alimentary Pharmacology & Therapeutics. 2013;37(5):505–516 Czuber-Dochan W, Norton C, Bassett P, Berliner S, Bredin F, Darvell M, Forbes A, Gay M, Nathan I, Ream E, Terry H. Development and psychometric testing of inflammatory bowel disease fatigue (IBD-F) patient self-assessment scale. Journal of Crohn's & Colitis. 2014;8:1398–1406